Association of HFE and TMPRSS6 genetic variants with iron and erythrocyte parameters is only in part dependent on serum hepcidin concentrations. Issue 9 (23rd July 2011) - Traglia, Michela; Girelli, Domenico; Biino, Ginevra; Campostrini, Natascia; Corbella, Michela; Sala, Cinzia; Masciullo, Corrado; Viganò, Fiammetta; Buetti, Iwan; Pistis, Giorgio; Cocca, Massimiliano; Camaschella, Clara; et al.
Abstract : Background: Hepcidin is the main regulator of iron homeostasis: inappropriate production of hepcidin results in iron overload or iron deficiency and anaemia. Aims: To study variation of serum hepcidin concentration in a normal population. Results: Hepcidin showed age and sex dependent variations that correlated with ferritin but not with serum iron and transferrin saturation. The size of the study population was underpowered to find genome wide significant associations with hepcidin concentrations but it allowed to show that association with serum iron, transferrin saturation and erythrocyte traits of common DNA variants in HFE (rs1800562) and TMPRSS6 (rs855791) genes is not exclusively dependent on hepcidin values. When multiple interactions between environmental factors, the iron parameters and hepcidin were taken into account, the HFE variant, and to lesser extent the TMPRSS6 variant, were associated with ferritin and with hepcidin normalised to ferritin (the hepcidin/ferritin ratio). Conclusions: The results suggest a mutual control of serum hepcidin and ferritin concentrations, a mechanism relevant to the pathophysiology of HFE haemochromatosis, and demonstrate that the HFE rs1800562 C282Y variant exerts a direct pleiotropic effect on the iron parameters, in part independent of hepcidin.